Effect of 20-hydroxyecdysone and haemolymph on oogenesis in the ixodid tick Amblyomma hebraeum - Seixas, Adriana; Friesen, Kevin; Kaufman, Reuben (My University, 2008)
Earlier work from our laboratory indicated that injection of 20-hydroxyecdysone (20E) into non-vitellogenic female Amblyomma hebraeum ticks stimulates the synthesis of vitellogenin (Vg), but not its uptake into oocytes [Friesen, K., Kaufman, W.R., 2004. Effects of 20-hydroxyecdysone and other hormones on egg development, and identification of a vitellin-binding protein in the ovary of the tick, Amblyomma hebraeum. Journal of Insect Physiology 50, 519–529]. In contrast, Thompson et al. [Thompson, D.M., Khalil, S.M.S., Jeffers, L.A., Ananthapadmanaban, U., Sonenshine, D.E., Mitchell, R.D., Osgood, C.J., Apperson, C.S., Roe, M.R., 2005. In vivo role of 20-hydroxyecdysone in the regulation of the vitellogenin mRNA and egg development in the American dog tick, Dermacentor variabilis (Say). Journal of Insect Physiology 51, 1105–1116] demonstrated that injection of 20E into virgin female Dermacentor variabilis ticks stimulated both vitellogenesis and Vg uptake into oocytes. In addition to the species difference in the two studies there were substantially different methods for injecting 20E. In our earlier work we injected small partially fed ticks after removing them from the host. Thompson et al. injected the females while they remained attached to the host. So in this study we repeated our earlier experiments on A. hebraeum using on-host injection. We also injected 20E into off-host ticks with or without haemolymph collected from engorged ticks (days 2–10 post-engorgement), or from large partially fed mated ticks in the rapid phase of engorgement, to see whether we might detect a ‘vitellogenin uptake factor’ (VUF) in haemolymph. Off-host injection of 20E (0.45 μg/g body weight (bw)) did not induce ovary development beyond that of vehicle-injected controls. But ticks in this study, receiving 20E plus haemolymph from engorged ticks, showed a significant increase in ovary weight beyond that of 20E alone (1.31 ± 0.05% bw; 34 for 20E plus haemolymph and 1.03 ± 0.05% bw; 25 for 20E alone). However, in normal engorged A. hebraeum, the ovary exceeds 7% bw at the onset of oviposition. As in our earlier work, in this study 20E stimulated Vg-synthesis (3.9 ± 0.5 mg Vt-equivalents/ml) beyond that occurring in vehicle-injected ticks (0.76 ± 0.14 mg Vt-equivalents/ml), and there was a further increase in ticks injected with 20E plus haemolymph from engorged ticks (8.9 ± 1.0 mg Vt-equivalents/ml). On-host injection of 20E alone (6 μg 20E/g bw) did not produce a statistically significant increase in oocyte length over that of vehicle-injected controls, whereas on-host injection of 20E plus engorged haemolymph resulted in significantly larger oocytes (261 ± 57 μm) compared to vehicle-injected controls (132 ± 11 μm), compared to 20E alone (131 ± 12 μm), or haemolymph alone (124 ± 24 μm). There was a marked stimulation of Vg-synthesis by 31 μg 20E/g bw (6.0 ± 1.5 mg Vt-equivalents/ml) compared to vehicle-injected controls (1.02 ± 33 mg Vt-equivalents/ml). Vt accumulation by ovaries was significantly greater in ticks treated with haemolymph (12 ± 3 μg Vt/mg ovary) or 20E plus haemolymph (56 ± 26 μg Vt/mg ovary) compared to vehicle-injected controls (5.1 ± 1.5 μg Vt/mg ovary). There was also a significant effect of 6 μg 20E/g bw plus engorged haemolymph on ovary weight (1.74 ± 0.29% bw) compared to vehicle-injected ticks (0.95 ± 0.10% bw), but not compared to ticks injected with 20E alone (1.25 ± 0.19% bw). We conclude that at least some of the differences observed between the two laboratories relate to the species difference, and that there is some evidence that the engorged haemolymph of A. hebraeum contains a VUF.
Keywords: ixodid ticks; amblyomma hebraeum; dermacentor variabilis; ecdysteroids; 20-hydroxyecdysone; vitellogenesis